2016
DOI: 10.1504/ijssm.2016.080465
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and sustainability in a large-scale healthcare improvement collaborative - seven propositions for achieving system-wide innovation and sustainability

Abstract: Change and reform in the healthcare system, and policy determination to reduce costs has now necessitated a rethink and more innovation for this sector. Leadership needs to strengthen professionals who have the dual responsibility for ensuring the quality and effectiveness of healthcare and this requires new organisational forms beyond the traditional hierarchical structures. Drawing upon strategic management and leadership discourse to underpin the study into sustainable and high performing healthcare systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…The IOCN network was a creative, innovative entity where resources were shared for the common good and which also enabled rapid learning and development while amplifying members’ effectiveness (Amoo et al , 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The IOCN network was a creative, innovative entity where resources were shared for the common good and which also enabled rapid learning and development while amplifying members’ effectiveness (Amoo et al , 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the IOCN’s case, this study identified the types of strategic challenges that must be attended to and explored how these vital issues were diagnosed by the network leaders before determining how these strategic challenges could be addressed. We found the recognition that place-based networks that sought to bring about system-wide change were a more sustainable entity (Amoo et al , 2016). Conversely, issues-based networks tend to focus more on single issues or a segment of the local population, that is, those with mental health problems or in the context of palliative medicine, such as variations in the cost of formal and informal health care for patients with advanced chronic disease, that is, refractory breathlessness (Dzingina et al , 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Place-based systems of care are increasingly proposed as vehicles for improving health and social care across a local population (Amoo et al, 2016), such as the Leeds Institute for Quality Healthcare (Mervyn and Amoo, 2014). Place-based networks have similarities and differences to narrowly defined issue-based networks such as Diabetes and Mental Health which strive for research uptake and seek to translate evidence into practice (Baker et al, 2009;Hanbury et al, 2010;Doyle et al, 2013).…”
Section: Place-based Systems Of Carementioning
confidence: 99%
“…The patient experience The patient experience Attention to leadership development Growing across OECD (OECD, 2017) Shifting to collaborative networks procedures and tools (Amoo et al, 2016;London Leadership Programme, 2017) Dyads to triads Admin: some pilot projects with physicians and nurses (e.g. Storkholm et al, 2017) Nurses: extensive (Appendix E:6) Physicians: beginning, integrated with clinical programs (Denis and van Gestel, 2016) Before promotion, limited to mentoring, projects Individual Dyads Admin: little mention Nurses: postgraduate studies and mentoring/projects Physicians: available post promotion but seemingly rarely followed up upon Initial development Early as part of initial training (Hirschfeld and Thomas, 2011;Sebastian, 2015) Later after promotion On-going development Co-production, self-reflection, inter-disciplinary teams (Darzi Fellowships, 2017/18) Learn the local context (Beer et al, 2016) Individually focussed Learn the local context Empowerment, enabling Bottom-up (high job satisfaction and retention) (Dahinten et al, 2014) Top down (some job dissatisfaction and frustration) Selection basis Personality assessment (MBTI), early self-selection Volunteering, later self-selection…”
Section: Focusmentioning
confidence: 99%